Students’ Critical Thinking Skills Through Project-Based Ethnochemistry Learning - Burhanudin Milama; Alma Nur Fitriana; Novi Yanthi (Jurnal Penelitian Pendidikan IPA, 2026)
Critical thinking skills are still a problem in chemistry learning. One of the causes is teaching strategies do not contextually link chemical concepts into everyday life. This study aimed to determine whether project-based ethno-chemistry learning affected students' critical thinking skills. The research method used a quasi-experimental with a nonequivalent control group design. Purposive sampling was conducted and resulted a sample size of 80 students, consisting of 40 students from class XI IPA 1 (Experimental group) and 40 students from class XI IPA 2 (Control group). The critical thinking test instrument consisting of 19 questions in the topic of colloid material. The results of Mann Whitney test showed a significant difference of critical thinking post-test score between the two groups (p = 0.000, p < 0.05). Thus, it can be concluded that project-based ethno-chemistry learning had an effect on students' critical thinking skills development. According to the n-gain score (57%), project-based ethno-chemistry learning was considered quite effective to develop students' critical thinking skills. The findings of this study contributed to the selection of various innovative teaching strategies which integrates local wisdom into project-based chemistry learning, so that critical thinking skills can be improved.